STUDI KOMPARASI HASIL BELAJAR MAHASISWA MELALUI METODE DARING DAN LURING PADA MATA KULIAH BAHASA INDONESIA - Ai Siti Zenab; Sary Sukawati (Jurnal Semantik, 2022)
This study aims to compare the results of offline and online learning methods based on the analysis of student learning scores. The method used in this research is a quantitative comparative study. Data collection was carried out after the offline and online learning processes were completed in different semesters. The research location is at Widyatama University. The research sample of first-year students for the 2019/2020 academic year was 36 students and the first-year students of the 2020/2021 school year were 29 students. The total sample is 77 students. The sample selected is level one because the subjects that are the object of research are at level one. The data used as research are the results of the student learning process in Indonesian language courses in the form of scores: 1) attendance, 2) task results, 3) UTS, and 4) UAS. This research was conducted by taking data on the results of the four components above during offline learning in 2019 and data on the results of scores during the online learning process in 2020. The data were analyzed by comparison using the SPPS test. The results obtained from this study are that there is a difference in the average passing grade between offline and online learning with a difference of 06.92 in value. Based on these results, it can be concluded that offline lectures produce higher lecture scores than online lectures.